2021
DOI: 10.1007/s00170-021-08157-1
|View full text |Cite
|
Sign up to set email alerts
|

Defects-per-unit control chart for assembled products based on defect prediction models

Abstract: Typically, monitoring quality characteristics of very personalized products is a difficult task due to the lack of experimental data. This is the typical case of processes where the production volume continues to shrink due to the growing complexity and customization of products, thus requiring low-volume productions. This paper presents a novel approach to statistically monitor defects-per-unit (DPU) of assembled products based on the use of defect prediction models. The innovative aspect of such DPU-chart is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…In the scientific literature regarding product assembly complexity, a model addressing the assessment of complexity from an objective standpoint was firstly proposed by Sinha et al (2012), and then used in several studies (Alkan et al 2017;Alkan 2019;Verna et al 2021aVerna et al , b, 2022a. In such a model, the molecular orbital theory developed by Huckel (1932) is applied to the engineering domain to analyze the complexity of cyber-physical systems.…”
Section: Structural Complexity Modelmentioning
confidence: 99%
“…In the scientific literature regarding product assembly complexity, a model addressing the assessment of complexity from an objective standpoint was firstly proposed by Sinha et al (2012), and then used in several studies (Alkan et al 2017;Alkan 2019;Verna et al 2021aVerna et al , b, 2022a. In such a model, the molecular orbital theory developed by Huckel (1932) is applied to the engineering domain to analyze the complexity of cyber-physical systems.…”
Section: Structural Complexity Modelmentioning
confidence: 99%
“…Referring to Sinha and de Weck's model, Alkan [7] and Verna et al [17] measured complexity of components through the time necessary to handle single parts, complexity of interfaces through the time for joining them and topological complexity through the energy of the product's adjacency matrix. Other researchers have recently presented statistical models to forecast product defects using product complexity indicators [1,5]. Differently, Mathieson [18] used graph theory (i.e., size, path length and decomposition)…”
Section: Product-centred Approachmentioning
confidence: 99%
“…A product consisting of many parts, and therefore with several tasks to assemble it, increases the risk of operator errors and thus defects. Many studies have shown that assembly complexity has a direct effect on the occurrence of product defects and on quality costs [1][2][3][4][5][6]. The aim of this paper is to provide an overview of the main methods used to assess assembly complexity in manufacturing contexts.…”
Section: Introductionmentioning
confidence: 99%
“…The use of molecular structures to represent real cyber-physical products is a well-established approach in the scientific literature. By using atoms to represent product components and bonds to represent connections, molecular models can effectively emulate real assembly and disassembly processes (Alkan et al ., 2017a,b; Alkan and Harrison, 2019; Sinha, 2014; Verna et al. , 2022a,b).…”
Section: Research Approachmentioning
confidence: 99%
“…By investigating the effects of product complexity on operator learning in assembly and disassembly processes, the study makes a significant contribution to the understanding of manufacturing technology and management, providing practical implications for businesses operating in a dynamic and complex manufacturing landscape. Unlike previous research that has primarily focussed on process performance metrics, such as time and defects (Alkan, 2019;Galetto et al, 2020a;Verna et al, 2022a), this study specifically investigates the implications of product complexity on operator learning. The extensive experimental campaign involving 84 operators and products with varying levels of complexity allows for a comprehensive analysis of these effects.…”
Section: Introductionmentioning
confidence: 99%